‘Where’s our #30peratus’: a feminist critical discourse analysis of Twitter debates on women's political representation - Yoong, Melissa (ISEAS–Yusof Ishak Institute, 2019)
This chapter draws on feminist critical discourse analysis to interrogate the ‘glass ceiling’ in Malaysian politics. Prior to GE14, women held only 10.8 per cent of parliamentary seats and 8.3 per cent of full ministerial posts. When presented with the opportunity to redress this gender gap, the winning alliance, Pakatan Harapan, failed to meet their election pledge to ensure that at least 30 per cent of policymakers are women. Presently, women constitute only 14.4 per cent and 19.2 per cent of legislators and full ministers respectively. This gender imbalance, however, did not meet much public criticism. It is this general acceptance of the status quo that is the focus of the present study. While research surrounding women’s low political representation in Malaysia has focused on the structural and cultural factors that inhibit opportunities for women within their parties, this study examines tweets from the #30peratus Twitter campaign led by women’s rights advocates to uncover the ideologies and discourses in the public sphere that justify hegemonic gender relations in Malaysian politics. The findings show that not only are patriarchal attitudes towards women politicians prevalent, but discourses endorsing patriarchal ideologies are often legitimised in terms of neoliberal and postfeminist discourses.